2018
DOI: 10.3892/mmr.2018.8831
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between autophagy levels in peripheral blood mononuclear cells and clinical parameters in patients with chronic obstructive pulmonary disease

Abstract: Autophagy serves a role in the pathogenesis of chronic inflammatory diseases. The aim of the present study was to compare the autophagy levels in the peripheral blood mononuclear cells (PBMCs) of patients with chronic obstructive pulmonary disease (COPD) and healthy individuals and to assess the association between autophagy and the clinical parameters of COPD. Samples of peripheral blood from 20 patients with stable COPD and 20 healthy controls were collected. PBMCs were harvested using Ficoll density gradien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…GD and FD patients exhibit chronic inflammation and elevated level of pro-inflammatory cytokines in blood [3, 4749], and it is unclear how chronic inflammation impacts SQSTM1/p62 level. For example, patients with chronic obstructive pulmonary disease (COPD) with increased levels of Il-6, Il-8, TNF-α demonstrated decreased levels of SQSTM1/p62 in PBMCs [50]. Our RT-PCR study demonstrated reduced mRNA level of SQSTM1/p62 in GD1 and FD PBMCs.…”
Section: Discussionmentioning
confidence: 74%
“…GD and FD patients exhibit chronic inflammation and elevated level of pro-inflammatory cytokines in blood [3, 4749], and it is unclear how chronic inflammation impacts SQSTM1/p62 level. For example, patients with chronic obstructive pulmonary disease (COPD) with increased levels of Il-6, Il-8, TNF-α demonstrated decreased levels of SQSTM1/p62 in PBMCs [50]. Our RT-PCR study demonstrated reduced mRNA level of SQSTM1/p62 in GD1 and FD PBMCs.…”
Section: Discussionmentioning
confidence: 74%
“…14 Another evidence suggested that autophagy can promote the release of inflammatory cytokines, which contributes to the inflammatory response of COPD. 15 However, extensive validations are needed to improve the understanding of autophagy in pathogenesis of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…17 Moreover, one previous study demonstrated that autophagy-associated protein levels of PBMCs in COPD patients were increased and were correlated with FEV 1 % predicted values and circulating levels of cytokines. 15 However, there are still few related studies in this field, and further investigations will be required to better understand this field.…”
Section: Discussionmentioning
confidence: 99%
“… 4 It can degrade damaged and degenerated macromolecules and organelles in the cytoplasm. 5 The degradation products can be recycled, providing the raw materials for normal cellular survival and metabolism. 5 However, excessive autophagy will induce excess cell damage, resulting in programmed cell death.…”
Section: Introductionmentioning
confidence: 99%